Stasiun Jatinegara Era Revolusi Kemerdekaan Indonesia 1945-1949 - Andi, Andi; Gunawan, Rudy; Sidik, Humar; Abdulhadi, Abdulhadi; Sudibyo, Sigit; Sulistyana, Ika Putri; Khofifatunnisa, Khofifatunnisa (Universitas Hamzanwadi, 2021)
Jatinegara, in this case Jatinegara Station, is one of the locations that has historical traces of a series of events defending the independence of the Republic of Indonesia from the threat of the Dutch Kingdom assisted by the Allies, represented by the British) in the era of the Indonesian independence revolution in 1945-1949. The purpose of this research is to raise the events surrounding the revolution for Indonesian independence at Jatinegara Station in 1945-1949. The method used in this research is the historical research method. The stages in historical research begin with heuristics, criticism, interpretation, and historiography or historical writing. The results showed that Jatinegara Station was involved in a number of events and state duties which were quite important for the continuity of the newly independent Republic of Indonesia. The incident, namely, the takeover of the power of the Railways/Railway Department in Jakarta (September 3, 1945), and the extraordinary Railway Events of the Indonesian President's Entourage Soekarno to Yogyakarta (January 3, 1946).Jatinegara dalam hal ini Stasiun Jatinegara adalah salah satu lokasi yang memiliki jejak sejarah serangkaian peristiwa mempertahankan kemerdekaan Republik Indonesia dari ancaman Kerajaan Belanda dibantu oleh pihak Sekutu, diwakili oleh Inggris) era revolusi kemerdekaan Indonesia tahun 1945-1949. Tujuan Penelitian ini adalah untuk mengangkat peristiwa-peristiwa seputar revolusi kemerdekaan Indonesia di Stasiun Jatinegara tahun 1945-1949. Metode yang digunakan dalam penelitian ini adalah metode penelitian sejarah. Tahapan dalam penelitian historis diawali dengan heuristik, kritik, interpretasi, dan historiografi atau penulisan sejarah. Hasil penelitian menunjukan bahwa Stasiun Jatinegara terlibat dalam sejumlah peristiwa maupun tugas kenegaraan yang cukup penting bagi kelangsungan Republik Indonesia yang baru saja merdeka. Peristiwa tersebut yaitu, pengambilalihan kekuasaan Perkeretaapian/Djawatan Kereta Api di Jakarta (3 September 1945), dan peristiwa Kereta Api Luar Biasa rombongan Presiden RI Soekarno ke Yogyakarta (3 Januari 1946)